Emas Anuar Sdn Bhd / Ain Fazira Syakila Anuar - Anuar, Ain Fazira Syakila (Universiti Teknologi MARA, Perlis, 2023)
As a final milestone of my degree journey in Universiti Teknologi MARA, I chose to pursue my industrial training at Emas Anuar Sdn Bhd. This report purposely disclosed to discover about company profile, SWOT analysis of the company and how the industrial training has been held there. The company has their internal and external environment that effect the performance. The internal environment include strengths and weaknesses. Sustainability of the company is one of the major strength and they should use this advantage to tackle more customers in the future. However, having gold jewellery business commonly have competitors that may provide comparable design quickly. This rivalry lead to lower chances to get even few customers. Emas Anuar Sdn Bhd should come out with new invention in marketing in order to attract more people coming to their physical and online store. External environment factor in the other hand can be controlled by strengthen quality of products and improve trust between brand and customer to ensure repetition of purchase occur. Social media range should be enlarged as well to draw more online customers. With that, online sales could be expanded. As the insurance premium for business organisations keep increasing, company should tackle the threat by asking the insurance company what they can do to prevent losses and since the company is consider as a big company, they are able to implement top-down safety risk management and mitigation measures to bring down costs.